DigiPrEP: A Pilot Trial to Evaluate the Feasibility, Acceptability, and Accuracy of a Digital Pill System to Measure PrEP Adherence in Men Who Have Sex With Men Who Use Substances. (1st February 2022) - Chai, Peter R.; Mohamed, Yassir; Bustamante, Maria J.; Goodman, Georgia R.; Najarro, Jesse; Castillo-Mancilla, Jose; Baez, Alejandro; Bronzi, Olivia; Sullivan, Matthew C.; Pereira, Luis M.; Baumgartner, Susan L.; Carnes, Tony C.; et al.
Abstract : Background: Adherence to once daily oral preexposure prophylaxis (PrEP) for HIV prevention can be challenging for men who have sex with men (MSM) with substance use. Digital pill systems (DPS) comprise a radiofrequency emitter integrated into a gelatin capsule containing PrEP, which transmits data to a wearable Reader following ingestion, thereby enabling direct, real-time adherence measurement. This study evaluated the feasibility, acceptability, and accuracy of a DPS to measure PrEP adherence. Methods: A 90-day, single-arm, open-label, pilot demonstration trial was conducted with adult, cisgender, HIV-negative MSM on PrEP with nonalcohol substance use. Feasibility was measured via DPS engagement and timeline followback. Acceptability was assessed via qualitative user experience interviews. Accuracy was evaluated via DPS performance metrics, pill counts, and DBS to quantify tenofovir diphosphate. Results: Sixteen MSM enrolled (median age, 32 years), and 15 completed the study. Engagement remained stable over time. Emergent nonadherence patterns included intercurrent substance use. The DPS was largely acceptable based on interviews; the predominant barrier to use was the Reader. DPS-recorded ingestions totaled 1099, including 83.9% were detected by Reader and 16.1% were reported manually. The DPS recorded 92.2% of 1192 total expected ingestions per pill counts. Point-biserial correlation (R = 0.58; 95% CI: 0.21 to 0.80; P = 0.047) and Pearson correlation (month 1: R = 0.85; 95% CI: 0.57 to 0.95; P = 0.0002; month 3: R = 0.75; 95% CI: 0.17 to 0.94; P = 0.0197) showed strong correlations between DPS-recorded adherence and tenofovir diphosphate in dried blood spots. Conclusion: DPS are a feasible, acceptable, and accurate method of measuring PrEP adherence in MSM with substance use. Future investigations should incorporate DPS into behavioral interventions targeting nonadherence. Abstract : Supplemental Digital Content is Available in the Text.